2018
DOI: 10.1093/chemse/bjy041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemoreceptive Abilities of the Hydrothermal Shrimp Mirocaris fortunata and the Coastal Shrimp Palaemon elegans

Abstract: Chemoreception might play an important role for endemic shrimp that inhabit deep and dark hydrothermal vents to find food sources and to locate active edifices that release specific chemicals. We compared the chemosensory abilities of the hydrothermal shrimp Mirocaris fortunata and the coastal related species, Palaemon elegans. The detection of diverse ecologically relevant chemical stimuli by the antennal appendages was measured with electroantennography. The 2 species can detect food-related odor and sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 86 publications
2
23
0
1
Order By: Relevance
“…2A, C, E). The cuticle of the setal shafts of aesthetascs is thin, especially more distally (Machon et al, 2018); and in our study, as in others on shrimp (e.g., Zhu et al, 2011;Zbinden et al, 2017;Krieger et al, 2020), this resulted in their collapsing when dried in a vacuum, despite our best efforts ( Fig. 2E).…”
Section: Sensory Systemssupporting
confidence: 76%
“…2A, C, E). The cuticle of the setal shafts of aesthetascs is thin, especially more distally (Machon et al, 2018); and in our study, as in others on shrimp (e.g., Zhu et al, 2011;Zbinden et al, 2017;Krieger et al, 2020), this resulted in their collapsing when dried in a vacuum, despite our best efforts ( Fig. 2E).…”
Section: Sensory Systemssupporting
confidence: 76%
“…Detection of odorant molecules was tested on Rimicaris exoculata (Renninger et al, 1995) and Mirocaris fortunata (Machon et al, 2018) through electrophysiology approaches. These studies showed that these two species can detect sulfide and organic stimuli (such as bacterial homogenates or dead shrimp TABLE 2 | Percentages of the reads corresponding to the dominant variants identified in this study, best BLAST hits and sequence similarities.…”
Section: Sensory Capacities In Hydrothermal Vent Shrimpmentioning
confidence: 99%
“…Carbon molecules produced by gill chamber epibionts have been shown to be transferred through the thin (0.5 µm) inner branchiostegite cuticle of R. exoculata, providing trans-tegumental nutrition (Ponsard et al, 2013). The very thin cuticle of the aesthetascs sensilla (0.5-1.5 µm at the apex in M. fortunata), as well as the pore-like structures occurring in the aesthetasc cuticle (Machon et al, 2018) could permit such transfer, allowing host cells to benefit from bacterial primary production. This would be of limited significance to the whole animal, but could be significant for nutrition of sensory cells.…”
Section: Do Bacteria Have a Specific Role For Shrimp?mentioning
confidence: 99%
See 1 more Smart Citation
“…Pada pelepasan material lama dan pengendapan material baru menjadi ciri aktivitas hydrothermal (49)(50)(51)(52),serta banyak mineral pembentuk proses yang melibatkan solusi, termasuk pelapukan dan diagenesa (18; 53). Hydrothermal merupakan suatu proses pembentukan mineral yang terjadi disekitar sumber dari panas bumi didalam kulit bumi yang terjadi akibat adanya injeksi dari magma terhadap air dengan kata lain terjadi pelarutan oleh magma sisa yang bercampur dengan air tanah sehingga mengalami pengkristalan (54)(55)(56)(57)(58)(59)…”
Section: Pendahuluanunclassified